2018
DOI: 10.1016/j.bbamem.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Gap junction gene and protein families: Connexins, innexins, and pannexins

Abstract: Gap junction channels facilitate the intercellular exchange of ions and small molecules. While this process is critical to all multicellular organisms, the proteins that form gap junction channels are not conserved. Vertebrate gap junctions are formed by connexins, while invertebrate gap junctions are formed by innexins. Interestingly, vertebrates and lower chordates contain innexin homologs, the pannexins, which also form channels, but rarely (if ever) make intercellular channels. While the connexin and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
135
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(139 citation statements)
references
References 57 publications
3
135
0
1
Order By: Relevance
“…It has been reported that these pathological conditions are related to the disruption of gap junction-mediated intercellular communications [25]. Gap junctions are composed of intercellular channels formed by connexins [26]. Increasing evidence indicates the importance of connexins in modulating the severity of inflammatory disease [27].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that these pathological conditions are related to the disruption of gap junction-mediated intercellular communications [25]. Gap junctions are composed of intercellular channels formed by connexins [26]. Increasing evidence indicates the importance of connexins in modulating the severity of inflammatory disease [27].…”
Section: Discussionmentioning
confidence: 99%
“…Gap junctions are plasma membrane domains containing arrays of intercellular channels that allow for the direct transfer of ions and small molecules (< ~ 1.2 kDa) between cells [1]. In vertebrates, gap junction channels are formed by a family of transmembrane proteins called connexins, which in humans constitutes 20 members [2]. Connexins are expressed in almost all cell types of the human body and have essential roles during development as well as in the adult organism.…”
Section: Introductionmentioning
confidence: 99%
“…The connexin genes form a close family displaying a large degree of amino acid identity and similarity within both the extracellular and transmembrane regions [10]. To date, the family of connexin genes is composed of 20 members within the mouse genome and 21 within the human genome, with 19 having clearly identifiable orthologs between both [11]. The genes are named starting with an abbreviation for gap junction, followed by their corresponding subgroup and order of discovery.…”
Section: Introductionmentioning
confidence: 99%